Facteur essentiel de performance en saut à la perche - Mesnard, M.; Morlier, J.; Cid, M. (Comptes Rendus Mécanique, 2007)
Most studies on pole-vaulting focus on energy transfer data but do not take into account all the actions exerted on the pole. Starting from experimental measurements, this study presents a three-dimensional mechanical model allowing the determination of the pole-vaulter's actions on the pole. The force and the moment exerted on the pole by the pole-vaulter during the last stride before take-off and during jump stage have been calculated. Then, a comparative study is carried out on two pole-vaulters having comparable morphologies and performing with the same pole, and points out the influence on performance of the moment applied to the pole.